Analisis dan Implementasi Marketing Analyst pada Website Ekatama Precast Indonesia - Sofyan Mufti Prasetiyo; Rizki Octavian; Nadha Ilham Taqbir Djuanda; Saiful Rohman (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Advances in technology can no longer be denied, now that they have changed the views, mindsets and habits of all levels of society, now almost every company has a Marketing Analyst, namely professionals who have the task of conducting data analysis in an effort to support the marketing business. The method used is using interviews and direct implementation at PT. Ekatama Precast Indonesia. The purpose of this research is to apply the mandate of the Marketing Analyst as a way to maximize marketing and promotion. The results of this study are that the implementation of Marketing Analyst using the SEO method is very influential on the website and makes the website one page of Google.